2015
DOI: 10.1111/anec.12319
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Cardiac Monitoring to Detect Atrial Fibrillation after Cryptogenic Stroke or Transient Ischemic Attack: A Meta‐Analysis of Randomized Controlled Trials

Abstract: Prolonged cardiac monitoring improves detection of atrial fibrillation and anti-coagulation use after cryptogenic stroke or TIA and therefore should be considered instead of shorter duration of cardiac monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…A previous RCT (CRYSTAL AF) has supported the prolonged cardiac monitoring and the results showed that AF was more frequently detected in patients with recent cryptogenic stroke (12.4% detection rate in the monitored group vs. 2% in the unmonitored group; HR 7.3; 95% CI 2.6-20.8; p < 0.001) [28]. In addition, a meta-analysis of RCTs showed improved detection of AF after cryptogenic stroke/TIA with prolonged cardiac monitoring [29]. Therefore, even in the presence of PFO, AF should be considered as a potential cause of some presumptive cryptogenic strokes.…”
Section: Discussionmentioning
confidence: 92%
“…A previous RCT (CRYSTAL AF) has supported the prolonged cardiac monitoring and the results showed that AF was more frequently detected in patients with recent cryptogenic stroke (12.4% detection rate in the monitored group vs. 2% in the unmonitored group; HR 7.3; 95% CI 2.6-20.8; p < 0.001) [28]. In addition, a meta-analysis of RCTs showed improved detection of AF after cryptogenic stroke/TIA with prolonged cardiac monitoring [29]. Therefore, even in the presence of PFO, AF should be considered as a potential cause of some presumptive cryptogenic strokes.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, patients with atrial fibrillation and previous stroke or TIA are at high risk (averaging 10% per year) of developing recurrent stroke107 Thus, a certain period of cardiac monitoring after stroke or TIA to look for atrial fibrillation seems reasonable. Compared with a shorter duration of monitoring, prolonged monitoring for seven days or more was shown to detect more atrial fibrillation in RCTs evaluating patients with stroke or TIA,50108109110111 but no difference in recurrent stroke was shown. However, these studies were not adequately powered to detect differences in clinical outcomes.…”
Section: Applications Of Newer Detection Methodsmentioning
confidence: 92%
“…Although prolonged cardiac monitoring has been shown to detect more atrial fibrillation in patients with ischemic stroke,50108109110111 the recommendations for its use are less certain in the guidelines as its clinical benefit and cost effectiveness remain uncertain. The AHA/ASA guideline stated that the clinical benefit of prolonged cardiac monitoring to detect atrial fibrillation after acute ischemic stroke is uncertain (class IIb) 118.…”
Section: Guidelinesmentioning
confidence: 99%
“…Several monitoring strategies have been investigated to detect asymptomatic AF after an ischemic stroke, including electrocardiography (ECG), in-hospital monitoring, Holter ECG of variable duration, external event or loop recorders, mobile cardiac outpatient telemetry, and implantable cardiac monitors. These studies, and their recent meta-analyses, [7][8][9][10][11][12] contributed significantly to our current understanding of the incidence of AF after ischemic stroke.…”
Section: Stroke Recurrence In Patients With Prior Cs and Esusmentioning
confidence: 98%